2008
DOI: 10.1309/2hgnj1gu57jmbjaq
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Intratumoral and Peritumoral Lymphatic Density and Blood Vessel Density in Invasive Breast Carcinomas

Abstract: We studied tumor lymphatic and vascular densities and lymphovascular invasion (LVI) as prognostic markers in 48 cases of invasive breast cancer treated with partial or total mastectomy and lymph node dissection. All cases were immunostained with D2-40 and CD31. Positively stained microvessels were counted in densely vascular/lymphatic foci (hot spots) at x400. The mean+/-SD peritumoral lymphatic microvessel density (LMD) was significantly higher than intratumoral LMD (9+/-7 vs 4+/-6; P< .01). There was a posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
50
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 33 publications
9
50
2
1
Order By: Relevance
“…It has been previously reported that LVD and MVD also result in poor prognosis in invasive ductal carcinoma (IDC) and colorectal cancer (Saad et al, 2006;El-Gohary et al, 2008), which is consistent with the results of this study. Therefore, D2-40 and CD34 are crucial to the generation and development of gastric cancer and may be used as effective indices to evaluate gastric cancer invasion, metastasis and prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…It has been previously reported that LVD and MVD also result in poor prognosis in invasive ductal carcinoma (IDC) and colorectal cancer (Saad et al, 2006;El-Gohary et al, 2008), which is consistent with the results of this study. Therefore, D2-40 and CD34 are crucial to the generation and development of gastric cancer and may be used as effective indices to evaluate gastric cancer invasion, metastasis and prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…[11][12][13] Although the significance of lymphatic vessel density is still unclear, it was proposed that tumor cells exposed to more lymphatic vessels are more likely to spread to lymph nodes and to distant sites. 21 Similar to previous studies, 6,26 we found that the presence of intratumor lymphatic vessels could be demonstrated in almost 50% of invasive breast carcinomas; however, the number of peritumor lymphatic vessels was significantly higher. As previously described in cervical and other cancers, 5,19 intratumor lymphatic vessels were characteristically small and flattened with a close lumen in contrast with the typically widely open, dilated lymphatics in peritumor regions.…”
Section: Discussionsupporting
confidence: 90%
“…Similar result was found by Schoppmann et al (2004) but not by El Ghohary et al (2008). In breast cancer, tumor size is the most powerful predictor for local recurrence, regional and systemic spread, therefore for overall survival.…”
Section: Discussionsupporting
confidence: 83%